2010
DOI: 10.17221/86/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

The impact of source restriction on yield formation of corn (Zea mays L.) due to water deficiency

Abstract: To understand the mechanisms causing yield limitations in defoliated plants subjected to water deficiency, the experiments were laid out as a randomized complete block design with split-plot arrangement. Soil-water regimes consisted of moderate irrigation until physiological maturity (W 1 ) or short severe water stress periods (W 2 ) at V 8 stage of ontogenesis, and tasseling which allotted to the main plots. Defoliation times (V 8 and tasseling) and intensities (cutting of one or two thirds of leaf blade) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The coefficient in all the treatments (T1-T5) was smaller than that in CK by as much as 50% in T3-T5, whereas the difference between CK and T1 and T2 in 2015 and T2 in 2016 was only 10-19% amount to CK (Figure 5e,f ). As reported, water stress leading to the reduction in grain yield was mostly due to a reduction in DM allocation to grains and not as much due to lower production of DM (Oveysi et al 2010). Currently effects of drought stress on carbon assimilation have been well considered in majority of crop growth models (Jones et al 2003, Saseendran et al 2014, while effects on DM partitioning were rarely considered (or considered empirically) due to an inadequate understanding of the partitioning process (Cavero et al 2000, Li et al 2006.…”
Section: Resultsmentioning
confidence: 99%
“…The coefficient in all the treatments (T1-T5) was smaller than that in CK by as much as 50% in T3-T5, whereas the difference between CK and T1 and T2 in 2015 and T2 in 2016 was only 10-19% amount to CK (Figure 5e,f ). As reported, water stress leading to the reduction in grain yield was mostly due to a reduction in DM allocation to grains and not as much due to lower production of DM (Oveysi et al 2010). Currently effects of drought stress on carbon assimilation have been well considered in majority of crop growth models (Jones et al 2003, Saseendran et al 2014, while effects on DM partitioning were rarely considered (or considered empirically) due to an inadequate understanding of the partitioning process (Cavero et al 2000, Li et al 2006.…”
Section: Resultsmentioning
confidence: 99%
“…Also in wheat and maize, individual grain mass could partly compensate for reduced grain numbers , Oveysi 2010) but did not always respond (Borras et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The unfavorable climatic conditions during the growing season of maize in 2006, that is, the dry period in June and July, may be the probable cause of lower yield compared to the situation in 2008 in all tillage variants, except for variant A. Also, Wilhelm and Wortmann (2004) and Oveysi et al (2010) have found a lower test weight of grain of maize and soybean in years with less precipitation during summer. In 2007, the drought period ensued in soybean seedfilling stage, and for this reason, both yield and the 1000 kernel weight were lowered compared with the same parameters in 2009.…”
Section: Discussionmentioning
confidence: 97%